Clinical guidelines for the management of inflammatory bowel disease: Update of a French national consensus. Issue 1 (January 2021) - Amiot, Aurélien; Bouguen, Guillaume; Bonnaud, Guillaume; Bouhnik, Yoram; Hagege, Hervé; Peyrin-Biroulet, Laurent; ,; Abitbol, Vered; Malamut, Georgia; Amiot, Aurelien; Boruchowicz, Arnaud; Bouguen, Guillaume; et al.
Abstract: Background: New treatments and therapeutic approaches repeatedly emerged in the field of inflammatory bowel disease. Aim: to update the French treatment algorithms for Crohn's disease (CD) and ulcerative colitis (UC). Methods: A formal consensus method was used to determine changes to the treatment algorithms for various situations of CD and UC. Thirty-seven experts voted on questions that had been drafted by the steering committee ahead of time. Consensus was defined as at least 66% of experts agreeing on a response. Results: Anti-TNF were reinforced as a first-line therapy rather than the use of immunosuppressant alone. Vedolizumab for UC, ustekinumab for CD took place as second-line maintenance therapy and potentially as a first-line therapy in the setting of unrestricted reimbursement for vedolizumab. Tofacitinib was recommended by the experts in case of vedolizumab failure for UC. Algorithms for complicated CD with abscess, intestinal and complex anal fistula were updated according to recent prospective cohort studies. Conclusion: The changes incorporated to the algorithms provide up-to-date and easy-to-use guidelines to treat patients with IBD.